2016
DOI: 10.1177/2050157916664558
|View full text |Cite
|
Sign up to set email alerts
|

Restricting mobile phone access during homework increases attainment of study goals

Abstract: Recent research has reported negative consequences, such as increased anxiety, associated with restricting people’s access to their mobile phones. These findings have led researchers to suggest that mobile phone use may pose a legitimately addictive behavior for some people. Other research has suggested negative effects of mobile phones on academic outcomes. To study the effects of phone separation on both anxiety and attainment of academic study goals, we randomly assigned participants ( N = 93) to a restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 30 publications
4
46
2
1
Order By: Relevance
“…In another study being unable to answer incoming calls on ones’ smartphone was found to cause increased heart rate and blood pressure, as well as feelings of anxiety and unpleasantness ( Clayton et al, 2015 ). Several other studies have examined smartphone restriction and potential addiction through various designs ( Sapacz et al, 2016 ; Cutino and Nees, 2017 ; van den Eijnden et al, 2017 ). These findings suggest that withdrawal symptoms may be in play when people’s access to their mobile phone is restricted.…”
Section: Introductionmentioning
confidence: 99%
“…In another study being unable to answer incoming calls on ones’ smartphone was found to cause increased heart rate and blood pressure, as well as feelings of anxiety and unpleasantness ( Clayton et al, 2015 ). Several other studies have examined smartphone restriction and potential addiction through various designs ( Sapacz et al, 2016 ; Cutino and Nees, 2017 ; van den Eijnden et al, 2017 ). These findings suggest that withdrawal symptoms may be in play when people’s access to their mobile phone is restricted.…”
Section: Introductionmentioning
confidence: 99%
“…These distracting effects of cell phone use in the classroom also extend to nearby students who are not using their cell phone (End, Worthman, Mathews, & Wetterau, ). These distractions have even led to the notion that cell phone usage is more disruptive than talking during classroom lectures, which can lead to students' impaired concentration and missing key class concepts (Aagaard, ; Cutino & Nees, ; King, Valença, & Nardi, ; Shaw, ; Wood et al, ). A second mechanism proposed for the negative effects of cell phone usage is suboptimal learning strategies, beyond poor attention.…”
mentioning
confidence: 99%
“…In addition to distractions in the classroom, the excessive use of cell phones has found to have some negative impacts on psychological well‐being. Research has challenged the idea of excessive cell phone use of being a clinical disorder (Cutino & Nees, ; Drouin et al, ). Other research found that even the absence of one's mobile device leads to increased anxiety and discomfort.…”
mentioning
confidence: 99%
“…Here, we propose that this negative effect might be explained by smartphone vigilance impairing another executive function, that of working memory. We argue that during vigilance, goals become activated, such as connecting to others (Kardos et al, 2018), that are competing with other goals in working memory, such as reading a paper (Cutino & Nees, 2016). In other words, once the phone vibrates, the notification activates the goal to pursue social or informational goals (i.e., checking the notification content), interfering with other goals kept in working memory (LaRose, 2015).…”
mentioning
confidence: 99%